Implementación de dos métodos de recuento en placa para la detección de colifagos somáticos, aportes a las metodologías estándar - Solano Barquero, Melissa (2012)
Two plate count methods, double layer and single layer of agar for quantification of somatic coliphages in water, were implemented using standard methodologies. Several variables were tested and provided valuable information that was not included in standard methodologies. The most important findings are described, such as the effect of using an excessively concentrated culture of E. coliand production of a log phase culture in only 4 hours of incubation, adjusting the concentration to an optical density of 0.3 at 600 nm (3.1 x 10 8 CFU / mL), or to McFarland 1 (3.0 x 108 CFU / mL). It was determined that coliphages controls must be stored at -70 °C to reduce its degradation. Quantities of reaction mixture exceeding 20 mL per Petri dish must be avoided to prevent interfere with bubbles during the counting of plate forming units (PFU). It was demonstrated that coliphages isolated from water samples can be stored for 48 hours at 4 °C without any degradation, and PFU are not observed in samples with high concentrations of coliphages, because a confluent lysis of the bacte-rial layer. There was no significant difference in the recovery of coliphages using doble layer or single layer methods, but such methods should be evaluated by means of controls, before applying them directly in the analysis of water samples.